Bioelectrocatalytic Reduction of Hydrogen Peroxide by Microperoxidase-11 Immobilized on Mesoporous Antimony-Doped Tin Oxide - Neumann, Bettina; Kielb, Patrycja; Rustam, Lina; Fischer, Anna; Weidinger, Inez M.; Wollenberger, Ulla (ChemElectroChem, 2017)
The heme-undecapeptide microperoxidase-11 (MP-11) was immobilized on mesoporous antimony-doped tin oxide (ATO) thin-film electrodes modified with the positively charged binding promotor polydiallyldimethylammonium chloride. Surface concentrations of MP-11 of 1.5 nmol cm−2 were sufficiently high to enable spectroelectrochemical analyses. UV/Vis spectroscopy and resonance Raman spectroscopy revealed that immobilized MP-11 adopts a six-coordinated low-spin conformation, as in solution in the presence of a polycation. Cathodic reduction of hydrogen peroxide at potentials close to +500 mV versus Ag/AgCl indicates that the reaction proceeds via a Compound I-type like intermediate, analogous to natural peroxidases, and confirms mesoporous ATO as a suitable host material for adsorbing the heme-peptide in its native state. A hydrogen peroxide sensor is proposed by using the bioelectrocatalytic properties of the MP-11-modified ATO.
CRIS-Team Scopus Importer:2022-04-14
Keywords: electrochemistry; enzyme catalysis; mesoporous materials; microperoxidase; spectroelectrochemistry